The Influence of Google Chrome Applications on Learning Independence: A Literature Review - Sya'af, Habib Chaliq; Bakti, Surya (LPPPI Publishing, 2025)
This study aims to analyze the influence of Google Chrome applications on students' learning independence, focusing on applications such as Google Docs, Google Classroom, and Google Meet. The method used is a literature review, by collecting and analyzing various relevant journal articles, books, and research reports published between 2014 and 2024. The results show that these applications make a significant contribution to supporting independent learning by providing tools for task management, collaboration, and flexible access to learning materials. Google Docs allows students to work collaboratively, while Google Classroom provides a platform for more structured learning management. Google Meet supports remote learning, allowing for in-person interaction between students and teachers. In addition, Google Chrome extensions such as PointerViz and Datasets2Tools enrich students' learning experience, allowing them to explore complex concepts independently. However, challenges related to privacy, data security, and cross-browser compatibility need to be addressed to maximize the use of these apps in support of self-paced learning. This study concludes that Google Chrome applications have great potential to increase learning independence, but there needs to be attention to technical and security aspects to support a more effective and safe learning experience.